Integration of halal management principles in modern business models: An analysis of implementation and impact of organizational performance in the halal industry sector of Thailand and Indonesia - Norman, Efrita; Sukarnoto, Toto; Cahyono, Heru; Nurdin, Muhammad Amin; Mohammad Fuad, Noor Aimi (Journal of Islamic, Social, Economics and Development, 2025)
This study explores the application of halal management principles in modern business models and analyzes their impact on organizational performance in the halal industry sector in Thailand and Indonesia. With the increasing global awareness of halal and strong market demand, understanding how halal management principles are applied and their impact on organizational performance is important. The study aims to provide in-depth insights into halal management practices and the factors influencing their success in two countries with different regulatory and social contexts. The research method used is qualitative with data collection techniques through in-depth interviews, participatory observation, and documentation analysis. Interviews were conducted with top managers, halal compliance officers, and halal industry stakeholders in Thailand and Indonesia. Participatory observations are conducted at the company's premises to learn about day-to-day practices, while documentation analysis involves reviewing relevant halal policies, certifications, and regulations. The data obtained were analyzed using thematic and narrative analysis techniques to identify key themes and patterns. The results show that companies that integrate halal principles effectively have experienced significant increases in market share, consumer confidence, and global competitiveness. In addition, the application of halal principles also opens up opportunities for expansion to the international market, especially among Muslim consumers. Nonetheless, the study also identified challenges such as the additional costs for certification and the complexity of adapting traditional business models. Overall, the integration of halal management principles in modern business models has proven to be an important strategy for improving organizational performance and ensuring long-term sustainability in the halal industry sector.